2020
DOI: 10.1101/2020.03.23.004135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmentally Induced Sperm RNAs Transmit Cancer Susceptibility to Offspring in a Mouse Model

Abstract: BackgroundDNA sequence accounts for the majority of disease heritability, including cancer. However, it is becoming clear that environmentally-induced epigenetic inheritance can also occur. Epidemiological studies have shown that maternal exposure to the pesticide DDT in pregnancy is associated with increased breast cancer risk in women. Yet, the effects of paternal exposure to this and other pesticides on the progeny’s breast cancer development has not been investigated.MethodsMale mice (c57bl/6) were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Moreover, the tumor phenotype was linked to regulation of the nutrient sensing mechanisms, with suppression of AMPK and increased mTOR activity in normal mammary tissues and tumors (40). Interestingly, another study from our lab showed that oral intake of the pesticide DDT in males also led to low birth weight and mammary tissue and tumor phenotypes, which were similar to those found for paternal malnutrition, including alterations in the energy sensing AMPK/mTOR axis, suggesting that there may be a common underlying mechanism for two distinct exposures (41). Paternally induced alterations in mitogenic pathways in daughter's mammary tissues are linked to epigenetic programing in DNA methylation and small non-coding RNAs such miRNAs and tRFs [ Table 1; (6,7,40)].…”
Section: Pre-conception Paternal Exposures and Epigenetic Inheritancementioning
confidence: 56%
See 4 more Smart Citations
“…Moreover, the tumor phenotype was linked to regulation of the nutrient sensing mechanisms, with suppression of AMPK and increased mTOR activity in normal mammary tissues and tumors (40). Interestingly, another study from our lab showed that oral intake of the pesticide DDT in males also led to low birth weight and mammary tissue and tumor phenotypes, which were similar to those found for paternal malnutrition, including alterations in the energy sensing AMPK/mTOR axis, suggesting that there may be a common underlying mechanism for two distinct exposures (41). Paternally induced alterations in mitogenic pathways in daughter's mammary tissues are linked to epigenetic programing in DNA methylation and small non-coding RNAs such miRNAs and tRFs [ Table 1; (6,7,40)].…”
Section: Pre-conception Paternal Exposures and Epigenetic Inheritancementioning
confidence: 56%
“…This will be a daunting task though, as population studies to identify epigenetic markers of ancestral exposure will likely take decades, given the temporal distance between the parental exposure and breast cancer onset in daughters. Another challenge to overcome and confirm findings from animal models in humans is the difficulty in ascertaining exposures in parents retrospectively, although data from our lab and others (40,41,55,61,72) suggest that different environmental insults alter the same non-coding RNAs in the male germline and could presumably be used as a marker of exposure if confirmed in humans. Studies on epigenetic inheritance of breast cancer in humans will also need to take into account the possible interaction between ancestral exposures with lifestyle and environmental factors after birth.…”
Section: Conclusion Unanswered Questions and Challengesmentioning
confidence: 90%
See 3 more Smart Citations